Microtensile bond strength of quartz fiber posts to different composite cores - Zahra Khamverdi; Shahin Kasraei; Mohadese Azarsina; Faeze Gheysari (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this in vitro study was to assess the microtensile bond strength of quartz fiber posts to different composites, and to composite combinations used as core materials. Thirty fiber posts were treated with a 24% hydrogen peroxide solution and silanized. The posts were divided into 5 groups according to the resin composite used as follows (n = 6): G1 - Ælite Flow (Bisco, Inc), G2 - Filtek Z250 (3M ESPE), G3 - Biscore (Bisco, Inc), G4 - Ælite Flow + Filtek Z250, G5 - Ælite Flow + Biscore. The resin composites were placed around the posts to produce cylindrical specimens. Two 1-mm² thick sticks containing the post in the center and composite cores on both ends were provided from each cylinder and tested for microtensile strength with a crosshead speed of 0.5 mm/min. One-way ANOVA and Tukey HSD tests were used for statistical analysis. Fractured surfaces were observed using a stereomicroscope with 20× magnification. Scanning electron microscopy (SEM) was used to evaluate the interface of the fractured sticks. The results showed that G2 had the highest bond strength values, and the lowest values were seen with G3. There were significant differences between groups 1, 2, 4 and groups 3, 5 (p < 0.05). Under the stereomicroscope, most of the failures were adhesive between the post and core material. Under SEM, Ælite and Z250 had smoother surfaces than Biscore, containing less porosities and voids.